Optimization of ultrasound-assisted extraction of two saponins from Paris polyphylla var. yunnanensis leaves using response surface methodology - Guo, Xianming; Qiao, Qing; Jin, Yutian; Lei, Huaxiong; Guo, Kunyao; Zhao, Zhengxiong; Li, Ping; Liu, Aizhong; Sun, Rui (Frontiers in Sustainable Food Systems, 2024)
Paris polyphylla var. yunnanensis is one of the famous Chinese herbs, in which two saponins (polyphyllin II and polyphyllin VII) have anticancer effects. The endangerment of Paris polyphylla var. yunnanensis, makes the study of optimizing the extraction of polyphyllin II and polyphyllin VII from the leaves of Paris polyphylla var. yunnanensis more important. The study established and optimized the process of ultrasound-assisted extraction for polyphyllin II and polyphyllin VII using the Box Behnken Design method of response surface methodology. The results showed that the optimum extraction conditions for polyphyllin II and polyphyllin VII are ethanol concentration of 73 and 70%, extraction temperature of 43 and 50°C, and number of extraction 3, respectively. Under the above conditions, the contents of polyphyllin II and polyphyllin VII were measured to be 6.427 and 19.015 mg/g (DW). The results showed that the experimental model fitted well, and the response surface methodology (RSM) was feasible to optimize the extraction process of polyphyllin II and polyphyllin VII from Paris polyphylla var. yunnanensis leaves. This method provides an effective approach for the comprehensive development and utilization of non-medicinal parts of Paris polyphylla var. yunnanensis.